2010
DOI: 10.1002/adfm.201001729
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic and Nanoscopic Three‐Phase‐Boundaries of Platinum Thin‐Film Electrodes on YSZ Electrolyte

Abstract: Agglomerated Pt thin films have been proposed as electrodes for electrochemical devices like micro‐solid oxide fuel cells (μ‐SOFCs) operating at low temperatures. However, comprehensive studies elucidating the interplay between agglomeration state and electrochemical properties are lacking. In this contribution the electrochemical performance of agglomerated and “dense” Pt thin film electrodes on yttria‐stabilized‐zirconia (YSZ) is correlated with their microstructural characteristics. Besides the microscopica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
97
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 28 publications
10
97
0
Order By: Relevance
“…YSZ membranes present thermo-mechanical stability through the whole intermediate temperature range (up to 700ºC), and reach the target value usually established for the Area Specific Resistance (ASR=0.15 Ωcm 2 , [11]) at temperatures as low as 400ºC [6,12]. However, despite the good performance achieved by the thin electrolytes themselves and the promising works reported on µSOFC devices (a maximum power density of 1037 mW/cm 2 was reported by Kerman et al [13]), the quick degradation shown by the typically implemented metallic electrodes [3,14] at operating temperatures still hinders the way to the commercialization of µSOFC devices [15][16][17]. A difficult balance between two opposite phenomena is required for the development of reliable metallic-based thin film electrodes, namely: (i) the promotion of thin film dewetting with temperature, in order to form a porous film and enlarge the triple phase boundary (TPB) length without losing the connectivity; (ii) the limitation of the dewetting process that makes the thin films unstable at operating temperatures.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…YSZ membranes present thermo-mechanical stability through the whole intermediate temperature range (up to 700ºC), and reach the target value usually established for the Area Specific Resistance (ASR=0.15 Ωcm 2 , [11]) at temperatures as low as 400ºC [6,12]. However, despite the good performance achieved by the thin electrolytes themselves and the promising works reported on µSOFC devices (a maximum power density of 1037 mW/cm 2 was reported by Kerman et al [13]), the quick degradation shown by the typically implemented metallic electrodes [3,14] at operating temperatures still hinders the way to the commercialization of µSOFC devices [15][16][17]. A difficult balance between two opposite phenomena is required for the development of reliable metallic-based thin film electrodes, namely: (i) the promotion of thin film dewetting with temperature, in order to form a porous film and enlarge the triple phase boundary (TPB) length without losing the connectivity; (ii) the limitation of the dewetting process that makes the thin films unstable at operating temperatures.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…As earlier mentioned, Figure 8 also includes ASR values for two different porous Pt/YSZ interfaces: (i) based on Pt/YSZ/Pt membranes under real µSOFC operating conditions from three different research groups [4,8,9]; (ii) based on porous Pt films deposited on YSZ single crystal as reported by Ryll et al [17].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Micro-SOFC operated with humidified natural gas reformed directly at the anode showed power density of 800 mW cm -2 at 530 °C [22]; however, this data was measured with an external heating source whereas the here reported power densities are achieved with self-sustained heating and on-chip reformed hydrogen which is directly fed to the micro-SOFC membranes. Considerably higher power densities are expected in case more stable electrodes are used that do not show agglomeration as well as the instability is prevented [20,44,45]. Also, different electrode materials than pure Pt are promising, whereby most of them are based on metals [12,21,25,45,46] and metal-ceramic composites [17,25,27,[47][48][49].…”
Section: Electrochemical Analysismentioning
confidence: 99%
“…Pt is known to have good electrochemical activity towards the reactants and can be easily deposited by sputtering technique, evaporation or PLD. The films deposited are typically dense and a thermal treatment is necessary to obtain the desired porosity, due to a phenomenon called dewetting [40][41][42] . Nevertheless, the dewetting also lead to a fast degradation of the Pt electrodes, causing the risk of loss of the electrical percolation at intermediate temperature (500ºC-800ºC) 43 .…”
Section: The Electrodesmentioning
confidence: 99%